PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL TEACHING AND LEARNING PERAWATAN WAJAH BERJERAWAT MANUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMKN 1 BUDURAN - Ningrum, Dini; Biyan Yesi Wilujeng; Maspiyah; Sri Dwiyanti (Jurnal Tata Rias, 2024)
Contextual, Teaching, and Learning is a learning design that connects knowledge from subjects with daily life to practice solving problems. This study aims to determine 1) the implementation of contextual, teaching, and learning syntax, 2) improvement of student’s learning outcomes of manual acne facial treatment, 3) student responses to the contextual, teaching, and learning design. It was a pre-experimental research and use pretest-posttest group design. The research subjects were students of class XI-Beauty Therapy at SMKN 1 Buduran which was carried out in 2 meetings. Data collection methode include observation results, cognitive and psychomotor learning test results, and questionnaires. The results of this research show 1) The syntax of contextual, teaching, and learning was implemented with percentage of 93.8% in the first meeting and 98.3% in the second meeting and it is in the outstanding category means the syntax is implemented well, 2) With paired t-tests on pre-test and post-test The significance value obtained (2-tailed) is 0.001, which is smaller than 0.05, which indicates that the contextual learning model has a significant difference in increasing learning outcomes in the average pre-test to post-test scores, namely from 67.3% to 89.6%. The percentage of student success rate on the psychomotor test is 100%. 3) Student responses to the application of the contextual, teaching, and learning design are shown by a percentage score of 83.3% which mean it is also in outstanding category. Based on the research results, contextual, teaching, and learning syntax was implemented and there was an improvement in student learning outcomes using the contextual learning model at both the first and second meetings with very good responses.